Violencia de pareja y desregulación emocional en adultos - Castilla Baez, César Sebastian (2024)
Intimate partner violence (IPV) is a factor associated with dissatisfaction within the relationship, bringing consequences for the victim such as depression, anxiety, substance abuse, suicidal ideation, etc. On the other hand, emotional dysregulation is understood as vulnerability and a lack of strategies to regulate emotions, which, among other aspects, prevents the individual from returning to their baseline emotional state. The objective of this study is to explore the relationship between the variables: Intimate partner violence and emotional dysregulation. A systematic search was conducted in three databases following the guidelines of the PRISMA guide (Page et al., 2021), and 10 articles were included, which met certain inclusion and exclusion criteria. As the main finding, it was determined that there is a relationship between emotional dysregulation and intimate partner violence. It is concluded that there is a positive relationship between emotional dysregulation and intimate partner violence, whether physical, sexual, or psychological. Cognitive-behavioral therapy and mindfulness interventions prove to be the most effective for the treatment of emotional dysregulation.